Banking Competition and Efficiency in Jordan: A Note (International Journal of Banking and Finance, 2012)
The financial economics literature contains numerous research papers which examine issues that concern the banking industry. One of these issues is banking competition. Indeed, this issue is important because of its complications to financial stability and the growth of the borrowing firms. The purpose of this paper is to assess the competitive behavior of the Jordanian banking sector during the period ranging from 1999 to 2008 using the non-structural test developed by Panzar and Rosse. In more specific terms, this paper examines the overall competitive condition during the period 1999 – 2008 and how it has evolved over time. Based on the empirical findings, it is expected that a number of policy recommendations may be provided. The objective of these recommendations is to enhance the regulation of the banking sector in Jordan and improve their performance.